Understanding survival challenges of Tamil Nadu leather industry through content analysis and AHP. Issue 2 (17th February 2020) - Hasan, Mohammad; Javed, Mohd Yousuf; Farooq, Ayesha
Abstract: Tamil Nadu leather industry has a strong bearing on the overall leather production of the country. So much so, that fluctuations in Tamil Nadu largely affect the overall performance of the Indian leather industry. Although, the southern region is performing far much better than Northern and Eastern region, there are still some pressing issues which need to be explored, analyzed and solved on a priority basis. Ample research is conducted in analyzing the overall performance of Indian leather industry including the Tamil Nadu cluster, yet the challenges faced by the business especially the small ones have yet not received considerable attention. This paper aims to explore issues prevailing in Tamil Nadu leather industry and understanding their underlying causes. The data has been gathered by conducting indepth interviews with experts in leather industry and crystallized the interview transcript by performing content analysis. Five main themes have been identified including decline in demand for leather products, difficulty in cost reduction, sensitive industrial situation, changing customer orientation and inadequate government support. These themes are then further divided into subthemes which are then analyzed through Analytical Hierarchy Method. Findings reveal that difficulty in cost reduction is the most pressing issue for the industry especially the production and compliance costs. The model proposed by the study highlights the major areas of concern in Tamil Nadu leather industry which need to work out on priority basis. Issues have been assigned respective weights which will make easier for the industrialists, academicians, and government to focus on the critical ones.